Analysis of factors influencing adherence to iron tablet consumption among pregnant women at Muara Enim Community Health Center: A cross-sectional study - Ferra Puspa Sari; Ali Harokan; Chairil Zaman (School of Health Sciences Al-Ma'arif, 2025)
Background Anemia in pregnancy remains a major global health concern, significantly affecting maternal and fetal outcomes. In Indonesia, particularly in Muara Enim, the prevalence of anemia among pregnant women has been increasing annually. Iron tablets are a key intervention for anemia prevention, yet adherence remains low. Objective This study aimed to analyze the factors influencing adherence to iron tablet consumption among pregnant women at Muara Enim Community Health Center. Methods This study employed a quantitative approach with an analytical survey design using a cross-sectional method. The research was conducted from April 24 to May 14, 2025, at Muara Enim Community Health Center. A total of 93 pregnant women were selected as respondents using purposive sampling from a population. Data were collected through structured interviews using a validated questionnaire comprising demographic characteristics and variables such as knowledge, attitude, economic status, husband support, and adherence to iron tablet consumption. Data were analyzed for descriptive statistics, bivariate analysis using Chi-square tests, and multivariate analysis through binary logistic regression to identify the most dominant influencing factor. Results The results showed that only 40.9% of respondents adhered to iron tablet consumption. Bivariate analysis revealed significant associations between adherence and knowledge (p=0.00), economic status (p=0.02), and husband support (p=0.04). Multivariate logistic regression identified husband support as the most dominant factor (OR=0.34; 95% CI: 0.13–0.88), indicating that women without husband support were 0.34 times less likely to adhere to iron tablet consumption. Conclusion Knowledge, economic status, and husband support significantly affect adherence to iron tablet consumption among pregnant women. However, husband support emerged as the most influential factor. It is recommended that antenatal education programs actively involve husbands to enhance support systems and improve adherence. Community-based interventions and cross-sector collaborations should be strengthened, especially for pregnant women with low socioeconomic status or limited family support